Effects of sulfamerazine on selected haematological and immunological parameters in rainbow trout (Onchorhynchus mykiss, Walbaum, 1792) - Saglam, Naim; Yonar, M. Enis (Wiley, 2009)
In the present study, effects of sulfamerazine on some haematological and immunological parameters of rainbow trout (Oncorhynchus mykiss) were examined. Four groups of rainbow trout were fed experimental diets containing either no sulfamerazine (control) or supplemented with sulfamerazine at 100 mg kg(-1) (Exp-A), 200 mg kg(-1) (Exp-B) or 400 mg kg(-1) (Exp-C) for 21 days. Blood samples were taken for the haematological and immunological parameters from fish on the third, seventh, 14th and 21st days of feeding. Haematological parameters [haematocrit, leucocrit, numbers of erythrocytes (RBC) and leucocytes (WBC), haemoglobin (Hb), mean corpuscular volume (MCV), mean haemoglobin concentration (MHC) and mean corpuscular haemoglobin concentration (MCHC)] and immunological parameters [phagocytic ratio (PR) and index (PI), glass-adherent NBT-positive cell activation, total plasma protein and total immunoglobulin (Ig)] were evaluated during the experimental trial. It has been observed that MCV (P < 0.05), PR and PI (P > 0.05) were increased and haematocrit and leucocrit value, numbers of erythrocytes and leucocyte, haemoglobin, MHC and MCHC values and total plasma protein and total Ig levels were decreased in rainbow trout after application of three different doses of sulfamerazine.
Keywords: rainbow trout; sulfamerazine; immunomodulation; haematological parameter; immunological parameter